Mechanisms of Drug Desensitization: Not Only Mast Cells - Vultaggio, Alessandra; Matucci, Andrea; Nencini, Francesca; Bormioli, Susanna; Vivarelli, Emanuele; Maggi, Enrico (Frontiers in Pharmacology, 2020)
Drug desensitization (DD) allows transient clinical tolerance to the drug in reactive patients and it is frequently and successfully used in the management of both IgE and non IgE-mediated hypersensitivity reactions (HRs). The underlying mechanisms behind this process is not well understood. The desensitization procedure is associated with the inhibition of mast cells degranulation and cytokine production, that, is attributable, at least partially, to the abrogation of Ca2+ mobilization; in vitro findings and in vivo mouse models of rapid desensitization show that the organization and spatial distribution of actin is critical for Ca2+ mobilization. Some clinical observations may suggest the induction of a longer memory of tolerance by DD and they raise the suspicion that other cells and mechanisms are involved in DD. Some data are emerging about the modifications of immune responses during DD in patients with previous immediate HRs. In particular, an increase of regulatory cytokines, mainly represented by IL-10, has been shown, and more importantly, the appearance of IL-35 producing T regulatory cells has been described during DD. The release of controlled cellular mediators by mast cells over time and the development of the antigen-specific regulation of adaptive response allow to safely and successfully reach the target dose of a first line drug during DD.